Análise crítica dos estacionamentos comerciais no centro de Curitiba - Komiya, Alvaro Massaharu (2014)
Nowadays, Curitiba has been claimed for a better urban mobility, whose protagonist is the car as individual transport. In this subject, the high rates of commercial parking lots in the town need to be highlighted. The argument of this work is that spaces destined to vehicles should add urban quality and economic diversification, in order to mitigate its negative social impacts. This research looks for find out the amount and distribution of parking in the city and qualifies them by existing concepts of urbanism, with the aim to discover the parking lots relations to environment and promote discussions about urban spaces consumed by car.